Researches on the geometrical and dimensional accuracy for complex thin parts made of electrical steel by abrasive waterjet machining. Issue 1 (1st November 2022) - Mihail, Laurenţiu-Aurel; Filip, Alexandru; Mija, Adrian
Abstract : The electrical steel laminations which compose the rotor and stator core for electrical motors have complex 2D shapes. When these parts require small batches of production, they can be efficiently manufactured only by flexible methods. The paper presents the results of using abrasive waterjet machining (AWJ) to obtain such parts within the frame of a research project with EU funding. The main objective of the research was the analysis of geometrical and dimensional accuracy of the parts which will confirm that AWJ is a suitable process in this case. The parts were measured on an optical digital profilometer. The measurement process was not simple because the parts are relatively large and cannot be focused only by one shot by the camera. Also, another important issue were the profile edges inconsistencies due to the burrs. Those problems and the limitations of the measurement technology did not allow the automation of measurement. The results and discussions proved that AWJ can be used successfully for manufacturing such parts and the machining process is traceable.